The history of broadcasting in the United Kingdom - Briggs, Asa 1921-2016 (Oxford Univ. Press, 1995)
Covering the period 1939 to 1945, this book discusses the impact of the Second World War on the BBC, and the role, which the BBC played within the history of the War. This is the third part of a five-volume history of broadcasting in the UK, giving an account of the rise of broadcasting in this country.
Published to Oxford Scholarship Online: March 2012